Biosensor for Hepatocellular Injury Corresponds to Experimental Scoring of Hepatosplenic Schistosomiasis in Mice. (8th June 2016) - Sombetzki, Martina; Koslowski, Nicole; Doss, Sandra; Loebermann, Micha; Trauner, Michael; Reisinger, Emil C.; Sauer, Martin
Abstract : Severe hepatosplenic injury of mansonian schistosomiasis is caused by Th2 mediated granulomatous response against parasite eggs entrapped within the periportal tissue. Subsequent fibrotic scarring and deformation/sclerosing of intrahepatic portal veins lead to portal hypertension, ascites, and oesophageal varices. The murine model of Schistosoma mansoni ( S. mansoni ) infection is suitable to establish the severe hepatosplenic injury of disease within a reasonable time scale for the development of novel antifibrotic or anti-infective strategies against S. mansoni infection. The drawback of the murine model is that the material prepared for complex analysis of egg burden, granuloma size, hepatic inflammation, and fibrosis is limited due to small amounts of liver tissue and blood samples. The objective of our study was the implementation of a macroscopic scoring system for mice livers to determine infection-related organ alterations of S. mansoni infection. In addition, an in vitro biosensor system based on the detection of hepatocellular injury in HepG2/C3A cells following incubation with serum of moderately (50 S. mansoni cercariae) and heavily (100 S. mansoni cercariae) infected mice affirmed the value of our scoring system. Therefore, our score represents a valuable tool in experimental schistosomiasis to assess severity of hepatosplenic schistosomiasis and reduce animal numbers by saving precious tissue samples.